Application of high concentration thulium-doped fiber for achieving S-band gain flattened hybrid optical amplifier - Emami, S.D.; Hajireza, P.; Abd-Rahman, F.; Abdul-Rashid, H.A.; Ahmad, Harith; Harun, Sulaiman Wadi (INOE, 2010)
A hybrid amplifier is proposed using a series configuration of Thulium-doped fiber (TDF) and Raman amplifiers, which shares the same pump laser. This amplifier covers the bandwidth of entire short wavelength band (S-band) region by combining the gain spectrum of the TDF and Raman amplifiers. The new method of gain flattening is suggested by adding a second stage amplifier with a high concentration TDF as a gain medium. The flat gain is theoretically obtained at around 24dB. The development of reliable high-power diode lasers in the 1420 nm wavelength range will make this type of wide-band hybrid amplifier an interesting candidate for S-band optical telecommunication systems.